Aspartate aminotransferase to platelet ratio index and sustained virologic response are associated with progression from hepatitis C associated liver cirrhosis to hepatocellular carcinoma after treatment with pegylated interferon plus ribavirin - Ng KJ; Tseng CW; Chang TT; Tzeng SJ; Hsieh YH; Hung TH; Huang HT; Wu SF; Tseng KC (Clinical Interventions in Aging, 2016)
Khai-Jing Ng,1,2,* Chih-Wei Tseng,1–4,* Ting-Tsung Chang,5,6 Shinn-Jia Tzeng,7 Yu-Hsi Hsieh,1,2 Tsung-Hsing Hung,1,2 Hsiang-Ting Huang,8 Shu-Fen Wu,9 Kuo-Chih Tseng1,2 1Department of Internal Medicine, Dalin Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, Chia-Yi, 2School of Medicine, Tzu Chi University, Hualien, 3Division of Gastroenterology, Department of Medicine, Taipei Veterans General Hospital, Taipei, 4School of Medicine, National Yang-Ming University, Taipei, 5Department of Internal Medicine, National Cheng Kung University Medical College and Hospital, Tainan, 6Infectious Disease and Signaling Research Center, National Cheng Kung University, Tainan, 7Department of Agronomy, National Chiayi University, Chia-Yi, 8Department of Nursing, Dalin Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, Chia-Yi, 9Institute of Molecular Biology, National Chung Cheng University, Chia-Yi, Taiwan *These authors contributed equally to this work Background: The aim of this study was to evaluate the clinically significant predictors of hepatocellular carcinoma (HCC) development among hepatitis C virus (HCV) cirrhotic patients receiving combination therapy.Patients and methods: One hundred and five compensated cirrhosis patients who received pegylated interferon plus ribavirin between January 2005 and December 2011 were enrolled. All the patients were examined with abdominal sonography and liver biochemistry at baseline, end of treatment, and every 3–6 months posttreatment. The occurrence of HCC was evaluated every 3–6 months posttreatment.Results: A total of 105 patients were enrolled (mean age 58.3±10.4 years). The average follow-up time for each patient was 4.38 years (standard deviation 1.73 years; range 1.13–9.27 years). Fifteen (14.3%) patients developed HCC during follow-up period. Thirteen of them had high baseline aspartate aminotransferase to platelet ratio index (APRI) (ie, an APRI >2.0). Multivariate analysis showed that those without sustained virologic response (SVR) (hazard ratio [HR] 5.795; 95% confidence interval [CI] 1.370–24.5; P=0.017) and high APRI (HR 5.548; 95% CI 1.191–25.86; P=0.029) had a significantly higher risk of HCC occurrence. The cumulative incidence of HCC was significantly higher (P=0.009) in patients without SVR (3-year cumulative incidence 21.4%; 95% CI 7.4%–35.5%; 5-year cumulative incidence 31.1%; 95% CI 11.2%–51.1%) compared to those with SVR (3- and 5-year cumulative incidence 6.2%; 95% CI 0%–1.3%). Further, the cumulative incidence of HCC was significantly higher (P=0.006) in patients with high APRI (3-year cumulative incidence 21.8%; 95% CI 8.2%–35.3%; 5-year cumulative incidence 30.5%, 95% CI 11.8%–49.3%) compared to those with low APRI (3- and 5-year cumulative incidence 4.2%, 95% CI 0%–1.0%).Conclusion: In HCV-infected cirrhotic patients who received combination therapy, APRI and SVR are the two major predictors of HCC development. Keywords: aspartate aminotransferase to platelet ratio index, chronic hepatitis C, hepatitis C virus, hepatocellular carcinoma, liver cirrhosis, sustained virologic response